African Americans in U.S. foreign policy : from the era of Frederick Douglass to the age of Obama - Heywood, Linda M. (Linda Marinda), 1945-; Blakely, Allison, 1940-; Stith, Charles R.; Yesnowitz, Joshua C. (University of Illinois Press, 2015)
"Bookended by remarks from African American diplomats Walter C. Carrington and Charles Stith, the essays in this volume use close readings of speeches, letters, historical archives, diaries, and memoirs of policymakers and newly available FBI files to confront much-neglected questions related to race and foreign relations in the United States. Why, for instance, did African Americans profess loyalty and support for the diplomatic initiatives of a nation that undermined their social, political, and economic well-being through racist policies and cultural practices? Other contributions explore African Americans' history in the diplomatic and consular services and the influential roles of cultural ambassadors like Joe Louis and Louis Armstrong. The volume concludes with an analysis of the effects on race and foreign policy in the administration of Barack Obama. Groundbreaking and critical, African Americans in U.S. Foreign Policy expands on the scope and themes of recent collections to offer the most up-to-date scholarship to students in a range of disciplines, including U.S. and African American history, Africana studies, political science, and American studies"--